1995
DOI: 10.1002/sce.3730790302
|View full text |Cite
|
Sign up to set email alerts
|

Wait‐time, classroom discourse, and the influence of sociocultural factors in science teaching

Abstract: Wait-time, a variable related to questioning in a teaching-learning situation, has been found to have implications for the inquiry mode of science teaching especially in Western classroom environments. Aside from the fact that the literature is very sparse in this area about what obtains in developing countries, nothing appears to be available with regard to how wait-time interacts with the sociocultural factors within non-Western science classrooms. In a non-Western country such as Nigeria where most science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Nevertheless, the ratio showed that chemistry teachers dominate the interaction during chemistry lesson. This was also reported by Jegede & Olajide (1995); Mohamed Najib & Mohammad Yusof (1995); and Galton et al, (1999) in their studies. It also suggests that teacher-pupil verbal interaction may be affected by authoritarian factor as proposed by Jegede and Olajide (1995).…”
Section: Five Main Categories Of Verbal Interactionsupporting
confidence: 79%
“…Nevertheless, the ratio showed that chemistry teachers dominate the interaction during chemistry lesson. This was also reported by Jegede & Olajide (1995); Mohamed Najib & Mohammad Yusof (1995); and Galton et al, (1999) in their studies. It also suggests that teacher-pupil verbal interaction may be affected by authoritarian factor as proposed by Jegede and Olajide (1995).…”
Section: Five Main Categories Of Verbal Interactionsupporting
confidence: 79%
“…This scenario was proven by the TSSI conducted with chemistry teachers. The interviews showed that chemistry teachers seldom conduct group discussions, and classroom verbal interactions are mainly dominated by the teacher (Jegede & Olajide, 1995). Teachers also rarely offer students the chance to reason out their answers (Foong & Daniel, 2013).…”
Section: Mastery Of Scientific Argumentation Between Individuals and mentioning
confidence: 99%
“…Wait-times have a strong relationship with socio-cultural attitudinal factors of traditional or non-westernized worldview (Jegede & Olajide, 1995), hence wait-times are culture-specific (Maroni et al, 2008;Nelson & Harper, 2006). For example, while Asian cultures seem to generally expect longer delays in turntaking, there are differences among Asian countries (Damron & Morman, 2011;Du-Babcock & Tanaka, 2010).…”
Section: Wait-timementioning
confidence: 99%